ASSESSMENT OF IMMUNOLOGICAL DISORDERS IN THE GENESIS OF BRONCHIAL ASTHMA IN CHILDREN WITH DIFFERENT DEGREES OF THE DISEASE CONTROLLABILITY - Литвинець, Л.Я.; Lytvynets-Golutyak, V.E.; Chopyak, V.V. (World of Medicine and Biology, 2020)
It is established that children with bronchial asthma may have pronounced changes in their immunological status, concerning both its cell and humoral components, and to a significant extent they are determined by the disease severity. In the examined patients with bronchial asthma, a limited reserve of phagocytic cells and their phagocytic activity have been established. The maximum inhibition of phagocytosis was observed in patients with uncontrolled bronchial asthma (p